2016
DOI: 10.1039/c6ob02236g
|View full text |Cite
|
Sign up to set email alerts
|

New one-pot synthesis of N-fused isoquinoline derivatives by palladium-catalyzed C–H arylation: potent inhibitors of nucleotide pyrophosphatase-1 and -3

Abstract: Various N-fused isoquinoline derivatives were synthesized using a new one-pot reaction of 1-bromo-2-(2,2-difluorovinyl)benzenes with N-H group containing heterocycles followed by intramolecular palladium-catalyzed C-H arylation. The method described gives convenient access to diverse structures of N-fused polycyclic isoquinolines. Sixteen of the synthesized compounds were screened as potential human nucleotide pyrophosphatase/phosphodiesterase 1 and 3 (h-NPP-1 and h-NPP-3) inhibitors. The most effective h-NPP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 71 publications
0
39
0
1
Order By: Relevance
“…7). 91 However, selectivity data vs. other ecto-nucleotidases have not been provided. The SAR studies showed that two methoxy groups at the 2-and 3-positions of the isoquinoline scaffold are important for the inhibitory activity.…”
Section: Non-nucleotide-based Npp1 Inhibitorsmentioning
confidence: 99%
“…7). 91 However, selectivity data vs. other ecto-nucleotidases have not been provided. The SAR studies showed that two methoxy groups at the 2-and 3-positions of the isoquinoline scaffold are important for the inhibitory activity.…”
Section: Non-nucleotide-based Npp1 Inhibitorsmentioning
confidence: 99%
“…In order to investigate the putative binding mode of the selective inhibitors in the homology models of human TNAP, human IAP, human NPP1 and human NPP3, docking studies were carried out. The crystal structure of any of the proteins was not available at the protein databank, therefore, homology models were prepared by our research group . Since these homology modelled structures do not contain any co‐crystallized ligand in their active sites, the site finder of MOE program was used for selection of binding site before molecular docking studies.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Transfection and Preparation of Membrane Fractions: The process of cell transfection was carried out initially by transfecting human alkaline phosphatase ( h ‐TNAP & h ‐IAP) expressing plasmids or human nucleotide pyrophosphatase/phosphodiesterase ( h ‐NPP1 & h ‐NPP3), expressing plasmids into the COS‐7 cells, respectively, in 10‐cm plates using Lipofectamine. In the next step, the cells were transferred to Dulbecco's modified Eagle's medium (DMEM) containing 6 µg of plasmid DNA and 24 µL of Lipofectamine reagent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these multiple possible roles, the biochemistry of NPP3 has not been extensively characterized, and the determinants of its substrate specificity are unknown. The 3D structures of all the other mammalian NPPs have been elucidated [11,[22][23][24][25][26][27][28], whereas NPP3 has been the subject of modeling studies to assist isozyme-specific inhibitor design [29][30][31]. Here, we report the crystal structure of human NPP3 as well as its complex with a substrate analog, and explore the dimerization properties of this enzyme.…”
Section: Introductionmentioning
confidence: 99%